Rapid measurement of serum caffeine concentrations in acuteclinical settings. Issue 1 (1st January 2021) - Hanazawa, Tomoki; Kamijo, Yoshito; Yoshizawa, Tomohiro; Usui, Kiyotaka
Abstract: The number of acute caffeine poisoning cases have increased in Japan. We can use serum caffeine concentrations to evaluate the severity of caffeine poisoning and determine whether or not we should perform hemodialysis. In this study, we sought to develop a rapid method for measuring serum caffeine concentrations. We used liquid chromatography-tandem mass spectrometry (LC-MS/MS) in the new method. We chose caffeine-d9 as the internal standard, and we used the standard addition method to quantify caffeine concentrations. We collected six blood samples from three patients with acute caffeine poisoning to measure serum caffeine concentrations. In our method, retention time for caffeine was 0.4 min, and the time required for the total LC-MS/MS analysis was 1 min per sample. We obtained accurate serum caffeine concentrations 7 min after injection into the LC-MS/MS instrument. Further, time-consuming sample pretreatment was not required because each sample was diluted 10, 000-fold. As a result, we could obtain serum caffeine concentrations for each patient in a total of 40 min. Our findings suggest that rapid, accurate measurement of serum caffeine concentrations by LC-MS/MS could contribute to real-time evaluation of poisoning severity and determination of appropriate therapeutic strategies in acute clinical settings.